Transformasi Desa Nglanggeran dalam Perspektif Jejaring Socio-Technical - Arianti, Mariata; Netra, Putri Aulia; Astari, Rahmita; Yuliar, Sonny (Jurnal Sosioteknologi, 2024)
This study analyzes the transformation of Nglanggeran village, Gunung Kidul Regency, in the Special Region of Yogyakarta. This village, which was before known as a desolate, impoverished, and water-scarce location, has been turned into an ecotourism hub that has won numerous accolades on a national and worldwide scale. This study employs a qualitative approach from a socio-technical perspective based on actor-network theory (ANT). ANT provides analytical tools that allow us to trace human-nonhuman associations as they proliferate and bring about socio-technical changes. The results of the analysis describe Nglanggeran's transformation in terms of phases, each of which is characterized by distinct socio-technical associations or networks. The first phase was aimed at instilling environmental consciousness within the community. In the second phase, the principles of ecotourism began to be gradually introduced into the community ethos. The third phase is characterized by the unification of diverse stakeholders in the advancement of ecotourism initiatives in Nglanggeran Village.This collective endeavor encompasses bolstering community trust, governmental endorsement, and the strategic integration of technology into ecotourism management paradigms. Each successive phase from inception to the present shows the increase of key actors, facilitating the transformation of Nglanggeran Village from post-disaster dilapidation to a state of enhanced welfare fostered by the auspices of ecotourism. The research findings attest to the multifaceted engagement of local and non-local actors in effectuating the transformation of Nglanggeran Village. Moreover, it is a socio-technical network in which various technical and natural resources from various sites (from the past and from overseas) are brought together to create a ‘new locality’ in Nglanggeran village.